Freeze-Thawing Effect on Fetal Haemoglobin Conformation and its Interaction with Liposomes - Timchenko, N. N. (Problems of Cryobiology and Cryomedicine, 2006)
There was studied a freeze-thawing effect on fetal haemoglobin conformation and interaction of its kinetics with phosphatidylcholine- and cardiolipin- formed liposomes. It has been found that freeze-thawing of fetal haemoglobin results in smoothing of temperature-dependent conformational changes in a molecule. Kinetic dependence of fetal haemoglobin and liposomes’ interaction practically does not change after the protein freeze-thawing.